2006
DOI: 10.1152/ajprenal.00227.2005
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic arginine-glycine-aspartic acid peptide inhibits macrophage infiltration of the kidney and carotid artery lesions in apo-E-deficient mice

Abstract: Elitok, Saban, Sergey V. Brodsky, Daniel Patschan, Tatyana Orlova, Kenneth M. Lerea, Praveen Chander, and Michael S. Goligorsky. Cyclic arginine-glycine-aspartic acid peptide inhibits macrophage infiltration of the kidney and carotid artery lesions in apo-Edeficient mice. Am J Physiol Renal Physiol 290: F159 -F166, 2006. First published August 16, 2005 doi:10.1152/ajprenal.00227.2005Interactions of leukocytes with the vascular endothelium culminating in their diapedesis represent not only a crucial event in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…For example, cilengitide is an antiangiogenic, cyclic RGD (cRGD) peptide that was originally identified as antagonists for the integrins α v β 3 and α v β 5 [84]. cRGD also limits leukocyte recruitment to sites of inflammation [85], reduces myeloid cell adhesion and transendothelial cell migration [86, 87]. When combined with OV, cRGD limited both OV-mediated inflammatory gene expression and CD45 leukocyte recruitment [18].…”
Section: The Interface Between Nk Cells and Oncolytic Viral Therapymentioning
confidence: 99%
“…For example, cilengitide is an antiangiogenic, cyclic RGD (cRGD) peptide that was originally identified as antagonists for the integrins α v β 3 and α v β 5 [84]. cRGD also limits leukocyte recruitment to sites of inflammation [85], reduces myeloid cell adhesion and transendothelial cell migration [86, 87]. When combined with OV, cRGD limited both OV-mediated inflammatory gene expression and CD45 leukocyte recruitment [18].…”
Section: The Interface Between Nk Cells and Oncolytic Viral Therapymentioning
confidence: 99%
“…Sytemically, injection of pretreated cells into postischemic C57Bl/6N mice completely protected animals from acute ischemic renal failure. To further confirm this data, we then pretreated the cells with combined 8-O-cAMP and the integrin receptor blocking peptide cyclic arginine-glycine-D-aspartic acid (cRGD) [68]. Administration of combined pretreated cells partly abrogated the former effects.…”
Section: Increasing Renoprotective Competence Of “Early Outgrowth”mentioning
confidence: 99%
“…This is in agreement with previous observations indicating that α5β1 is the predominant receptor for fibronectin in monocytes (44), and that α5β1 is implicated in monocyte influx into inflamed sites (18). Interestingly, it has been shown that cyclic RGD peptides were capable of decreasing macrophage infiltration in kidneys and in carotid artery lesions of apo-E-deficient mice (45). Neutrophils, which are considered to be critical mediators in acute inflammatory liver injury (7), were also depressed in the cyclic RGD peptide treated steatotic OLTs.…”
Section: Discussionmentioning
confidence: 99%